2020
DOI: 10.1186/s12903-020-01310-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PTH and corticotomy on implant movement under mechanical force

Abstract: Background Osseointegrated implants are considered as clinically non-movable. Parathyroid hormone (PTH) is known to play a significant role in the regulation of bone remodeling and in intermittent, low doses, result in osteoanabolic effects. This study aimed to investigate the effects of PTH and corticotomy, both under traction force, on osseointegrated implants. Methods Four implants—two in each hemimandible—were placed in each of the three study mongrels. Each mongrels were designated as control, normal do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…2 ). 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27
Fig. 2 Hormones related to bone formation and resorption.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27
Fig. 2 Hormones related to bone formation and resorption.
…”
Section: Methodsmentioning
confidence: 99%
“…A study on mongrels found increased levels of bone remodeling around dental implants inserted in the mandible, in the group administered PTH. 25 An application perhaps close to clinical utilization is presented in a paper investigating PTH-coated titanium dental implants in rats. 105 The results were promising, with increased bone formation around the PTH-coated implants.…”
Section: Methodsmentioning
confidence: 99%
“…74 PTH-induced bone remodelling upregulation and corticotomy in dental implant site preparation with additional functional forces may impose a risk on the displacement of an osseointegrated implant. The study by Kim et al 75 demonstrated that various procedures, such as surgical, pharmacological and application of functional forces, might alter the catabolic and anabolic balance of osseointegrated implants in bone remodelling.…”
Section: Parathyroid Gland Disordersmentioning
confidence: 99%